Evaluation of the pharmacotherapeutic follow-up in patients admitted with high obstetric risk in the University Hospital of Guayaquil - Fajardo Vélez, Betsy; Arias Duque, Luis Armando; Garcia Larreta, Frella Soraya (Revista Universidad de Guayaquil, 2021)
The use of drugs during pregnancy has become increasingly frequent, this is because during this period various physiological changes occur that could affect pre-existing diseases or induce specific disorders of pregnancy, so it is necessary to promote a Active pharmacovigilance through pharmacotherapeutic monitoring. This document is the result of the research carried out at the Guayaquil University Hospital on patients who were admitted with high obstetric risk in the period from January to June 2021, where the different diagnoses could be classified according to the age range, level of risk and problems related to the medication provided during the hospital stay. The main objective of the research is to evaluate the effectiveness of pharmaceutical care through pharmacotherapeutic follow-up during the period established for the study. The work was carried out through the unit dose dispensing service, using as main instruments: the pharmacotherapeutic profile recorded daily during the stay in the hospitalization service of the patients, the registration of pharmaceutical interventions and the review of medical records. The total of profiles prepared was 144 and the Drug Related Problems(DRP) detected were 82, the most frequent being DRP 1 (54.87%) followed by DRP 5 (15.85%); It was determined that the age range with the highest incidence in terms of obstetric risk is between 25 and 30 years, with 26.38% of the obstetric risks found.